An introduction to information theory symbols, signals & noise - Pierce, John R. 1910-2002 (Dover Publications, 1980)
Covers encoding and binary digits, entropy, language and meaning, efficient encoding and the noisy channel, and explores ways in which information theory relates to physics, cybernetics, psychology, and art. Uncommonly good...the most satisfying discussion to be found. ? Scientific American. 1980 edition.